2017
DOI: 10.7196/331
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of the ICU nurse in the antimicrobial stewardship team at a private hospital in KwaZulu-Natal, South Africa

Abstract: Background. Care of the critically ill patient has become increasingly challenging, with a rising incidence of resistant pathogens resulting in the ineffectiveness of many antibiotics. Severe infection is associated with prolonged intensive care unit (ICU) length of stay, and increased morbidity, mortality, and healthcare costs. Antimicrobial stewardship (AMS) aims to prevent resistance and protect patients and the wider community by promoting correct antimicrobial use. The current AMS literature has failed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 12 publications
0
20
0
2
Order By: Relevance
“…4: No discussion of recruitment criteria for interview No. 6: Lacking discussion of relationship between researchers and participants [ 31 ] Rout J The role of ICU nurses in antimicrobial stewardship at a South African private hospital 17 Healthcare professionals (doctors, nurses and pharmacists in ICU/surgery) 8/9 No. 6: Lacking discussion of relationship between researchers and participants [ 19 ] Torres NF Patterns of self-medication in Maputo city, Mozambique 49 Healthcare professionals (pharmacists) and pharmacy customers 9/9 No points lost [ 24 ] Agardh C Using pharmacists and drugstore workers as sexual healthcare workers among MSM in Dar es Salaam, Tanzania 15 Drugstore customers (men who have sex with men) 9/9 No points lost [ 29 ] Asante KP Knowledge of antibiotic resistance and prescription practices in the Brong Ahafo Region of Ghana 33 Healthcare professionals (doctors, physician assistants, nurses and community health officers) 8/9 No.…”
Section: Resultsmentioning
confidence: 99%
“…4: No discussion of recruitment criteria for interview No. 6: Lacking discussion of relationship between researchers and participants [ 31 ] Rout J The role of ICU nurses in antimicrobial stewardship at a South African private hospital 17 Healthcare professionals (doctors, nurses and pharmacists in ICU/surgery) 8/9 No. 6: Lacking discussion of relationship between researchers and participants [ 19 ] Torres NF Patterns of self-medication in Maputo city, Mozambique 49 Healthcare professionals (pharmacists) and pharmacy customers 9/9 No points lost [ 24 ] Agardh C Using pharmacists and drugstore workers as sexual healthcare workers among MSM in Dar es Salaam, Tanzania 15 Drugstore customers (men who have sex with men) 9/9 No points lost [ 29 ] Asante KP Knowledge of antibiotic resistance and prescription practices in the Brong Ahafo Region of Ghana 33 Healthcare professionals (doctors, physician assistants, nurses and community health officers) 8/9 No.…”
Section: Resultsmentioning
confidence: 99%
“…Os estudos ainda apontam outras situações em que se fazem necessárias que o enfermeiro intensivista atue como defensor dos pacientes e familiares, como por exemplo: nas reuniões de família (Ahluwalia et al, 2015), nos aspectos que envolvem o paciente possível doador de órgãos (Forsberg et al, 2015), nas questões que permeiam a presença ou não da família dentro da UTI (Pasek & Licata, 2016), uso correto de antimicrobianos no tratamento de infecções (Rout & Brysiewicz, 2017), pacientes em fim de vida (Becker et al, 2017, Borowske, 2012, como também, perante uma internação por ordem judicial na UTI (Luz et al, 2019).…”
Section: Discussionunclassified
“…Ainda, o enfermeiro age como defensor do paciente, e ao mesmo tempo como articulador, no que diz respeito à terapêutica medicamentosa, quer seja para tratamento de infecções, quando o enfermeiro avalia a resposta do paciente ao tratamento com antibióticos, e discute a eficácia destes com o médico (Rout & Brysiewicz, 2017), quanto em relação aos cuidados do paciente em final de vida, quando faz a mediação junto ao médico, para que o paciente receba medicação adequada para o controle de sintomas agudos, e assim, possa ter uma morte pacífica (Becker et al, 2017).…”
Section: Discussionunclassified
“…Specifically, the results suggested that the "role" of the nurse should include ensuring appropriate antimicrobial use (including the assurance of correct duration and prevention of overuse), a good working (and up to date) knowledge of antimicrobial guidelines, and education (e.g., educating colleagues and patients about use and challenging prescribing decisions). In a more focused setting, Rout and Brysiewicz (2017) highlighted the essential role of the intensive care unit (ICU) nurse within the AS team as vital to the success of AS in the ICU. The four categories found in the study were advocacy, organizational, clinical, and collaborative roles of the nurse.…”
Section: Role Of the Nurse In Antimicrobial Stewardshipmentioning
confidence: 99%